2004
DOI: 10.1017/s0022112004001041
|View full text |Cite
|
Sign up to set email alerts
|

Choked flows in open capillary channels: theory, experiment and computations

Abstract: This paper is concerned with flow-rate limitations in open capillary channels under low-gravity conditions. The channels consist of two parallel plates bounded by free liquid surfaces along the open sides. In the case of steady flow the capillary pressure of the free surface balances the differential pressure between the liquid and the surrounding constant-pressure gas phase. A maximum flow rate is achieved when the adjusted volumetric flow rate exceeds a certain limit leading to a collapse of the free surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 8 publications
0
31
0
Order By: Relevance
“…Ichikawa et al, 2004;Jong et al, 2007;Zhu and Petkovic-Duran, 2010) and grooved/triangular (Yost and Holm, 1995;Romero and Yost, 2006;Baret et al, 2007). Moreover, the same approach has been taken for channels defined by hydrophilic paths on a hydrophobic substrate (Darhuber et al, 2001) and by the space between two parallel plates (Rosendahl et al, 2004) under the assumption of flow with low Reynolds number and liquid imbibing in a tube/slablike manner. When channels are mounted vertically gravity becomes important and exact analytical solutions for capillary imbibition are no longer possible in general.…”
Section: Introductionmentioning
confidence: 99%
“…Ichikawa et al, 2004;Jong et al, 2007;Zhu and Petkovic-Duran, 2010) and grooved/triangular (Yost and Holm, 1995;Romero and Yost, 2006;Baret et al, 2007). Moreover, the same approach has been taken for channels defined by hydrophilic paths on a hydrophobic substrate (Darhuber et al, 2001) and by the space between two parallel plates (Rosendahl et al, 2004) under the assumption of flow with low Reynolds number and liquid imbibing in a tube/slablike manner. When channels are mounted vertically gravity becomes important and exact analytical solutions for capillary imbibition are no longer possible in general.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the change in methanol flow rate cannot eliminate the effect of gravity. Moreover, research shows that the liquid/gas fluid flow in microgravity conditions is significantly different from that in normal gravity conditions because of the absence of the gravity [42][43][44][45][46]. Therefore, PEMFCs may show distinct types of behavior in a reduced gravity environment.…”
Section: Introductionmentioning
confidence: 99%
“…in Jaekle 1991Jaekle , 1993. Rosendahl et al (2004) found a flow limitation in open capillary channels which is similar to choking in compressible duct flows and open channel flows under gravity. In this work we want to expand this theory to other channel geometries.…”
Section: Introductionmentioning
confidence: 69%